Computer Assisted Language Learning (CALL) Activities and the Students’ English Oral Proficiency - Zaida K. Ulangkaya (RIRAI Publisher, 2021)
The study aimed to determine the impact of Computer Assisted Language Learning Activities to the oral English Proficiency of JEEP 1 students. The students' pre and post mean scores were compared to determine the significant improvement in their oral English proficiency. This research made used of the experimental research design with pre and post-test design with 58 randomly selected students from different year levels who were enrolled at Mindanao State University- Maguindanao and currently taking the subject JEEP 1 of the S.Y. 2014-2015. The instrument used covered four specific areas as Sentence Reading, Reading and Pronunciation, Comprehension and Structure, and Sentence Repetition. The following are the summary of the findings: 1. Before the CALL Activities in JEEP 1, the students’ oral English proficiency is lower elementary as indicated by the mean of 0.60; After engaging to the CALL Activities, the students’ oral English proficiency is still lower elementary as proven by the mean score of 0.79; and After comparing the results, it was found out that there is a substantial transformation in the students' oral English proficiency level before and after Computer Assisted Language Learning Activities in JEEP 1 as indicated by the t-Value of 2.84. Based on the results of the study, it was determined that CALL Activities have contributed slight improvement to the student’s oral English proficiency score. However, the said activities did not improve their oral English proficiency level possibly due to some unknown factors that might have affected them during the duration of the study.